Tata kelola dokumen kehukuman berbasis pengintegrasian dengan jaringan dokumentasi dan informasi hukum - Akbar, Zulfikar; Prijana, Prijana; Rodiah, Saleha (Perpustakaan Universitas Gadjah Mada, 2024)
Introduction. The integration of legal document management at PTKIN with JDIH is necessary to ensure legal certainty. This research aims to describe the process of managing legal documents and information integrated with JDIH within PTKIN. Data Collection Methods. This research uses qualitative methods with a case study approach. Data collection process were carried out by observations, interviews, and document reviews. There were from informants selected through a purposive approach. Data Analysis. Data analysis process were carried out by reducing data, presenting data, and conclusions. Results and Discussion. The management of legal documents at UIN Sunan Gunung Djati Bandung comprises three elements as per Permenkumham RI No.8/2019 and four phases of integration. These phases begin with the preparation of the Terms of Reference for the establishment of the JDIH institution and end with the official release from JDIHN, which is related to the jdih.uinsgd.ac.id website. Conclusion. The governance of legal documents integrated with JDIH involves three elements: abstracting, processing, and reporting. UIN Sunan Gunung Djati Bandung’s integration with JDIH is considered as a pioneerin Indonesia’s PTKIN scope, making it a reference for other PTKINs in managing legal documents.